Hubungan Sikap Perawat dengan Pelaksanaan Identifikasi dalam Patient Safety di Ruangan Rawat Inap Rumah Sakit Royal Prima Jambi - Nurhayati; Risna Meliyani; Aulia Ratnasari Harahap (Nightingale: Journal of Nursing, 2026)
Background: Patient safety is the most important indicator in the health care system, which is expected to be a reference in producing optimal health services and reducing incidents for patients. Patient safety is a system or service arrangement in a hospital that provides patient care so that patients become safer. Patient safety in hospitals starts from accurate patient identification. Methods This research method is an observational analytical survey using a cross sectional approach which was carried out in the Inpatient Room of Royal Prima Jambi Hospital in September 2023. The sampling technique was total sampling with a total sample of 36 respondents. Results: The results of this research were obtained from 36 respondents, nurses' attitudes were poor, 5 people (38.5%) carried out patient identification in patient safety poorly and 8 people (61.5%) performed quite well. The majority of respondents showed good nursing attitudes, carrying out identification in patient safety quite well as many as 9 people (39.1%), good 11 people (47.8%), and very good 3 people (13%). The results of the Spearman Rho analysis show a value of r = 0.680 with a p value of 0.001, where if the value of r = 0.50-0.69 the relationship is strong.